High Spatial Resolution Imaging of Endogenous Hydrogen Peroxide in Living Cells by Solid‐State Fluorescence. (13th July 2016) - Lindberg, Eric; Winssinger, Nicolas
Abstract: Herein, we describe selective imaging of hydrogen peroxide using a precipitating dye conjugated to a boronic acid‐based immolative linker. We achieved visualization of endogenous hydrogen peroxide in phagosomes by solid‐state two‐photon fluorescence imaging in living cells with exceptionally high spatial resolution. Abstract : H2 O2 w it works : Selective imaging of hydrogen peroxide in phagosomes was achieved by using a precipitating dye and a boronic acid‐based linker. Using this method, we were able to visualize endogenous hydrogen peroxide by solid‐state two‐photon fluorescence imaging in living cells with exceptionally high spatial resolution.